2020
DOI: 10.3390/brainsci10070469
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Correlates of a Single Session of Prefrontal tDCS in Patients with Prolonged Disorders of Consciousness: A Pilot Double-Blind Randomized Controlled Study

Abstract: Background. Transcranial direct current stimulation (tDCS) over the left dorsolateral prefrontal cortex (lDLPFC) was reported to promote the recovery of signs of consciousness in some patients in a minimally conscious state (MCS), but its electrophysiological effects on brain activity remain poorly understood. Objective. We aimed to assess behavioral (using the Coma Recovery Scale—Revised; CRS-R) and neurophysiological effects (using high density electroencephalography; hdEEG) of lDLPFC-tDCS in patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 37 publications
2
58
1
Order By: Relevance
“…Further trials confirmed clinical effects (as measured by behavioral improvements observed on the CRS-R), even if moderate, of tDCS applied over the DLPFC, especially for MCS patients [12][13][14][15][16][17]. However, the clinical effects seem inconsistent as several J o u r n a l P r e -p r o o f trials showed no relevant behavioural improvements using the same type of montage [18][19][20] or multichannel montages [21].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 68%
See 2 more Smart Citations
“…Further trials confirmed clinical effects (as measured by behavioral improvements observed on the CRS-R), even if moderate, of tDCS applied over the DLPFC, especially for MCS patients [12][13][14][15][16][17]. However, the clinical effects seem inconsistent as several J o u r n a l P r e -p r o o f trials showed no relevant behavioural improvements using the same type of montage [18][19][20] or multichannel montages [21].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 68%
“…For instance, Luna et al found a modulation of alpha power that was different according to the region stimulated and was not correlated with changes in performance [22]. In another recent pilot study, Carrière and colleagues identified a tendency for higher power in the alpha and theta band at the group level after active tDCS and higher connectivity in the alpha band between left and right parietal regions, and in fronto-parietal regions [19]. In a study investigating tDCS with TMS-EEG [20], reduced slow-wave activity and response slope were found following tDCS; both these measures are proxies of cortical bistability and correlated with J o u r n a l P r e -p r o o f high-frequency suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al ( 42 ) observed a trend toward higher EEG functional connectivity in frontal areas after 2 weeks of tDCS over the right and left DLPFC. More recently, Carrière et al ( 37 ) assessed weighted phase-lag index (wPLI), symbolic mutual Information (wSMI), and EEG power bands changes following anodal tDCS over the L-DLPFC in 13 MCS patients. They observed higher wSMI connectivity between left and right parietal regions, and higher fronto-parietal wPLI connectivity, although these changes only appeared when uncorrected for multiple comparisons.…”
Section: Effects Of Tdcs On Brain Functionmentioning
confidence: 99%
“…Transcranial direct current stimulation [28][29][30][31][32][33][34][35][36]. DLPFC or posterior parietal cortex at 10-20 min/time (1-2 mA for 10-20 days) was chosen.…”
Section: Neurostimulation Therapymentioning
confidence: 99%